The Relationship between Knowledge, Community Action and Home Environmental Conditions with Malaria Incidence in the Community Health Center Work AreaIdanogawo, Nias Regency, Nias Regency - Ganda Murni Yanti Zebua (Paspama Institute, 2023)
Indonesia is one of the countries in the world that still faces the risk of malaria. Idanogawo subdistrict is one of the malaria endemic areas in Nias district, North Sumatra with the Annual Parasite Incidence (API) figure in 2019 reaching 100%. The transmission of malaria is caused by the bite of female Anopheles mosquitoes and humans which is supported by the conditions of the home environment. The aim of this research is to determine the relationship between knowledge, community actions and home environmental conditions and the incidence of malaria in the working area of the Idanogawo Health Center, Idanogawo District, Nias Regency 2021. Research This is an analytical research with a cross sectional study. The population in this study is 250 people who visit the Idanogawo health center working area and a sample of 71 people using the Slovin formula and sampling can be done using simple random sampling technique. The results of the research show that there is a relationship knowledge and the incidence of malaria (p=0.013), there is a relationship between community action and the incidence of malaria (p=0.012), and there is a relationship between environmental conditions and the incidence of malaria (p=0.000). It was concluded that knowledge, community actions and home environmental conditions showed a relationship with the incidence of malaria, so it was recommended that health workers carry out outreach to the community, evaluate malaria programs, wear closed clothing when going out at night, and clean the home environment.